Mathematical modelling for earth sciences - Yang, Xin-She (Dunedin, 2008)
Mathematical modelling and computer simulations are an essential part of the analytical toolset used by earth scientists. In this textbook, designed for use by mathematicians and non-mathematicians encountering the application of mathematics to the earth sciences for the first time, Dr Yang has carefully selected topics which will be of most value to students. The book is designed to be 'theorem-free' and whilst balancing formality and practicality.